A note on the impact of hours worked on mortality in the OECD - Edvard Johansson (The Research Institute of the Finnish Economy (ETLA), 2003)
In this note we investigate whether an increase in hours worked per employed person raises the total mortality rate in a sample of 23 OECD countries during 1960-1997. We use the same basic research design and data as Gerdtham & Ruhm (2002). This implies that the total mortality rate is modelled to depend on economic conditions, demographic characteristics, year effects, country effects, and country-specific time trends. We extend the analysis by allowing the mortality rate to depend on, in addition, the number of hours worked per employed individual. Surprisingly, we find that an increase in the number of hours worked actually has a negative and statistically significant effect on the total mortality rate, even when controlling for income. Although one possible explanation may be that fluctuations in hours of work in fact is, in this setting, more a measure of the capacity utilisation rate of the economy than a measure of how stressful work is for individuals who are actually working, more research on the topic is needed in order to find a plausible explanation for the observed phenomenon. – Mortality ; Business Cycles ; Health – – Tässä artikkelissa tutkitaan, onko työntekijäkohtaisten tehtyjen työtuntien kasvulla kuolleisuutta lisäävä vaikutus 23 OECD-maassa 1960-1997 välisenä aikana. Tarkastelussa Käytetään Gerdthamin ja Ruhmin (2002) kehittämää mallia, ja suurilta osin myös samaa aineistoa. Tämä tarkoittaa, että taloudellisen suhdannetilanteen, demografian, kiinteiden vuosi- ja maaefektien, sekä maakohtaisten aikatrendien oletetaan vaikuttavan kuolleisuuteen. Alkuperäistä mallia laajennetaan siten, että edellä mainittujen muuttujien lisäksi myös tehtyjen työtuntien vaikutus otetaan huomioon. Tuloksien mukaan kuolleisuus ei näytä kasvavan tehtyjen työtuntien myötä vaan kuolleisuus näyttää yllättäen laskevan tehtyjen työtuntien määrän kasvaessa. Tämä tulos pätee, vaikka tarkastelun kohteena olevien maiden tulotaso otetaan huomioon. Tutkimuksen tulos saattaa johtua siitä, että tehdyt työtunnit kuvaavat itse asiassa talouksien käyttöastetta enemmän kuin työn kuormittavuutta. Tämän havainnon selvittämiseksi tarvitaan kuitenkin lisää tutkimusta. – Kuolleisuus ; Suhdanteet ; Terveys
Keywords: E32; I12; 330; Arbeitszeit; Sterblichkeit; Konjunktur; Gesundheit; OECD-Staaten